Effect of Liquid Organic Fertilizer Derived from Catfish Offal Waste and Banana Pseudostems on the Growth of Curly Chili Pepper (Capsicum annuum L. var. longum) - Anggraini, Septika; Wakhidah, Anisatu Z. (Bioscientist : Jurnal Ilmiah Biologi, 2026)
This study aimed to analyze the effect of liquid organic fertilizer (LOF) derived from catfish offal waste and banana stems on the vegetative growth of curly chili (Capsicum annuum L. var. longum). The study employed an experimental method using a randomized block design (RBD) with four treatments: P0 (control), P1 (20 mL LOF/L), P2 (40 mL LOF/L), and P3 (60 mL LOF/L), each with six replications. The LOF was applied at a rate of 200 mL per plant weekly. The observed parameters included plant height, leaf number, and leaf width over a four-week period, and the data were analyzed using one-way ANOVA followed by a post hoc test. The results showed that the LOF contained 0.08% N, 0.09% P, and 15.9 mg/L K, and had a significant effect on all measured parameters (Sig. < 0.05). Treatment P1 produced the best results, increasing plant height by 59.9%, leaf number by 43.2%, and leaf width by 21.2% compared with the control. The decline in growth at higher doses indicates the potential for phytotoxicity or nutrient imbalance. Therefore, this organic waste-based LOF was effective at low to moderate doses in enhancing the early vegetative growth of curly chili.